Influence of T6 heat-treating and over-ageing on out-of-phase thermo-mechanical fatigue behaviors of Al-Si-Cu alloy. (December 2022) - Khisheh, S.; Azadi, M.; Hendoabadi, V. Zaker; Parast, M.S. Aghareb; Winter, G.; Seisenbacher, B.; Gruen, F.; Khalili, K.
Abstract: In this study, the Influence of the T6 heat-treating and over-ageing process on the material behavior of cylinder head Al-Si-Cu alloy under out-of-phase thermo-mechanical fatigue at maximum temperatures of 250–350 °C was investigated. The specimen is subjected to a conventional T6 process that includes a 5 h solution at 510 °C, an air quench, and 3 h of ageing at 200 °C, some specimens (with and without the T6 process) were over-aged at 250 °C for 100 h. The fracture surfaces of specimens under thermo-mechanical fatigue (TMF) conditions are examined using scanning electron microscopy (SEM). The Al-Si-Cu alloy exhibited a ductile characteristic, as shown by the SEM images. The quick cyclic softening happened early in the TMF cyclic stress response behavior, and afterward, the cyclic stress remained steady at decreasing strain amplitudes. Cracks in TMF damage behavior were mostly initiated by broken and debonded Si and intermetallic phases, and they commonly nucleated near the primary Si-matrix interface. The T6 treatment improved the fatigue lifetime considerably under TMF loadings for non-over-aged alloys. However, the T6 treatment had no significant effect on the over-aged alloy. Graphical Abstract: ga1 Highlights: The material hardened and softened at < 250 °C, but softened at > 250 °C. The A380-T6 alloy has more cyclic softening than the A380-T0 alloy (without heat-treating). The reduction in crack initiations and the absence of fatigue striations indicated a slower propagation rate. Temperature affected the softening rate due to dislocation annihilation and rearrangement. T6 enhanced fatigue lifetime in non-over-aged alloys, but not in over-aged alloys.